Rare Metastatic Pattern: Serous Ovarian Carcinoma Mimicking Primary Breast Cancer – Two Case Reports - Aidarov , Askar; Khaidarov , Saker; Bolatbekova, Raikhan; Kaidarova , Dilyara; Aidarov, Daulat; Ossikbayeva , Sahia; Goncharova, Tatyana; Aidarova , Aray; Sadykova , Assel D; Seiduanova, Laura; Tazhibayeva , Karlygash (Bangladesh Journal of Medical Science, 2025)
Background High-grade serous ovarian carcinoma (HGSOC) is the most aggressive and most common subtype of epithelial ovarian cancer (OC). Metastases to the breast from malignant neoplasms of other origins are extremely rare, accounting for only 0.5–2% of all breast cancer cases. The metastatic spread of HGSOC to the breast is exceptionally uncommon, representing only 0.07% of all ovarian cancer metastases. Objective is to analyze the clinical characteristics, diagnostic methods, treatment strategies, and outcomes of rare cases of HGSOC metastasizing to the breast. Case presentation The study describes two rare cases of HGSOC metastasizing to the breast, recorded in 2024 at the Almaty Oncology Center. Immunohistochemical (IHC) tissue analysis played a key role in diagnosis. In one case, a 57-year-old patient responded well to treatment, which included neoadjuvant chemotherapy, subtotal mastectomy, and adjuvant targeted therapy. CA-125 levels normalized, and PET imaging showed no metabolically active lesions. In contrast, a 52-year-old patient with HGSOC metastases to the breast and peritoneal carcinomatosis experienced disease progression despite undergoing segmental mastectomy, laparoscopic biopsy, and palliative therapy, leading to death two months after diagnosis. Conclusion Timely diagnosis using advanced imaging techniques and IHC, along with a multidisciplinary approach, are key factors in improving clinical outcomes. This study presented two clinical cases of HGSOC metastasizing to the breast. In the first case, early diagnosis and a comprehensive treatment approach stabilized the patient’s condition, leading to the absence of detectable tumor activity. In contrast, delayed diagnosis and rapid disease progression in the second case resulted in a poor outcome. BJMS, Vol. 24 No. 03 July’25 Page : 1007-1013